2023
DOI: 10.3390/agriculture13020230
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Wind Field and Deposition Effect of a Novel Air-Assisted Strawberry Sprayer

Abstract: Strawberry is a widely cultivated cash crop in China. In order to control pests and diseases on strawberries, there must be sufficient deposits on the abaxial surfaces of the leaves. Air-assisted technology can effectively increase the deposition on the abaxial surfaces of the leaves; however, most air-assisted equipment is not suitable for application due to the pattern of strawberry planting. Therefore, a novel air-assisted strawberry sprayer was developed, the static and dynamic wind fields were measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Whether it is the vortex airflow from unmanned aerial vehicle or the parallel airflow from an air‐assisted boom‐sprayer, wind loads are applied to the branches and leaves of the crop canopy by higher wind speeds, forcing flexible branches and leaves to bend and deform, increasing porosity and opening the transport channel for droplets to enter the interior of the crop canopy 43–45 . The droplets can be forced to change their trajectory inside the branch and leaf apertures by the airflow 46–49 . However, research has shown that using vortex airflow can cause more blade displacement and branch disturbance compared to parallel airflow 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether it is the vortex airflow from unmanned aerial vehicle or the parallel airflow from an air‐assisted boom‐sprayer, wind loads are applied to the branches and leaves of the crop canopy by higher wind speeds, forcing flexible branches and leaves to bend and deform, increasing porosity and opening the transport channel for droplets to enter the interior of the crop canopy 43–45 . The droplets can be forced to change their trajectory inside the branch and leaf apertures by the airflow 46–49 . However, research has shown that using vortex airflow can cause more blade displacement and branch disturbance compared to parallel airflow 14 .…”
Section: Resultsmentioning
confidence: 99%
“…[43][44][45] The droplets can be forced to change their trajectory inside the branch and leaf apertures by the airflow. [46][47][48][49] However, research has shown that using vortex airflow can cause more blade displacement and branch disturbance compared to parallel airflow. 14 Therefore, the rotor wind mode chosen in this paper is more favorable for improving droplet deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Spray deposition on the leaf abaxial surface has been the focus of increasing research attention in recent years ( Maski and Durairaj, 2010 ; Owen-Smith et al., 2019 ; Jiang et al., 2023 ). Air-assisted spraying has been shown to achieve superior deposition on the abaxial surface of leaves in practical application ( Christovam et al., 2010 ; Sinha et al., 2020 ; Xu et al., 2023 ). However, most previous studies have been conducted to test the performance of sprayers.…”
Section: Discussionmentioning
confidence: 99%
“…This helps farmers determine the most suitable local crops and the best planting time and sowing quantity [4] . In addition, it can also analyze the planting experiment data, so as to master the actual vitality of the seeds, improve the emergence rate, and improve the disease resistance and yield of the crops [5] .…”
Section: Application In Agricultural Productionmentioning
confidence: 99%